Pre-post changes of integrated care needs in patients undergoing bariatric surgery - Paul, Cinara; Friederich, Hans-Christoph; Zech, Ulrike; Wild, Beate (International journal of obesity, 2025)
Patients undergoing bariatric surgery have complex bio-psycho-social needs which require integrated care. This study aimed to evaluate changes of integrated care needs from pre- to one-year post-surgery and to identify baseline variables associated with integrated care needs at follow-up.
Gesehen am 28.08.2025